Correlation Between p16/Ki-67 Expression and the Grade of Cervical Intraepithelial Neoplasias. (July 2020) - Mandal, Rananjit; Ghosh, Ishita; Banerjee, Dipanwita; Mittal, Srabani; Muwonge, Richard; Roy, Chinmayi; Panda, Chinmay; Vernekar, Manisha; Frappart, Lucien; Basu, Partha
Abstract : Interpretation of histopathology of cervical premalignant lesions suffers from marked interobserver variability due to its subjective nature. We aimed to evaluate the usefulness of the biomarkers p16 and Ki-67 in improving the diagnostic accuracy of cervical histopathology and assess the correlation between p16 expression and human papillomavirus test in different grades of cervical intraepithelial neoplasia (CIN). Cervical tissue specimens with a diagnosis of CIN 1 or worse (CIN 1+) on hematoxylin and eosin staining were selected for immunohistochemistry (IHC) staining for p16 and Ki-67. The IHC slides were examined by a gynecologic pathologist along with a review of hematoxylin and eosin slides. The review histopathology diagnosis was used to correlate with the IHC results. We observed that the proportion of women with overexpression of p16 increased with increasing histologic severity: 0% in women with normal histology; 33.3% in women with CIN 1; 58.1% in women with CIN 2; and 73.8% in women with CIN 3. Among the human papillomavirus–positive women, 76.3% (58/76) women with CIN 2/CIN 3 expressed p16, and only 8.9% (4/45) women with normal histopathology or CIN 1 expressed the same. A combination of p16 positivity and abnormal expression of Ki-67 beyond the lower third of the epithelium was observed in 0% of normal/CIN 1 and 60.5% (40/66) of CIN 3 detected on routine histopathology. We concluded that dual staining could be used as an adjunctive test to improve the diagnostic accuracy of histopathology. In addition, p16/Ki-67 IHC has a role in guiding management decisions in cases with discordant colposcopy and histopathology diagnoses.